On the Modeling of Pension Expenditures in Europe. Issue 1 (2nd January 2020) - Ntotsis, Kimon; Papamichail, Marianna; Hatzopoulos, Peter; Karagrigoriou, Alex
Abstract: The purpose of this work is the modeling of public pension expenditures as percentage of cross domestic product (GDP) of various European countries. For this purpose, we proceed to locate, collect and analyze the factors which either on short term or on long term may have an impact on the shaping of this variable. By achieving that we are able to model the pension expenditures and make forecasts. The analysis focuses on 20 European countries for which a large amount of data are available including a set of 20 possible explanatory variables for the period 2001–2015.